Just the Facts: Protected code blue – Cardiopulmonary resuscitation in the emergency department during the coronavirus disease 2019 pandemic. Issue 4 (July 2020) - McIsaac, Sarah; Wax, Randy S.; Long, Brit; Hicks, Christopher; Vaillancourt, Christian; Ohle, Robert; Atkinson, Paul
Abstract : Emergency medical services (EMS) is called for a 65-year-old man with a 1-week history of cough, fever, and mild shortness of breath now reporting chest pain. Vitals on scene were HR 110, BP 135/90, SpO2 88% on room air. EMS arrives at the emergency department (ED). As the patient is moved to a negative pressure room, he becomes unresponsive with no palpable pulse. What next steps should be discussed in order to protect the team and achieve the best possible patient outcome?